Aromatic C-H bond activation revealed by infrared multiphoton dissociation spectroscopy - Jašíková, Lucie; Hanikýřová, Eva; Schröder, Detlef; Roithová, Jana (Journal of mass spectrometry, 2012)
Metal-oxide cations are models of catalyst mediating the C-H bond activation of organic substrates. One of the most powerful reagents suggested in the gas phase is based on CuO(+) . Here, we describe the activation of the aromatic C-H bonds of phenanthroline in its complex with CuO(+) . The reaction sequence starts with a hydrogen atom abstraction by the oxygen atom from the 2-position of the phenanthroline ring, followed by OH migration to the ring. Using infrared multiphoton spectroscopy, it is shown that the reaction can be energetically facilitated by additional coordination of a water ligand to the copper ion. As the reaction is intramolecular, a spectroscopic characterization of the product is mandatory in order to unambiguously address the reaction mechanism.